Implementasi Kebijakan Badan Layanan Umum Daerah: Studi Kasus RSUD dr. Soemarno Sosroatmodjo Tanjung Selor Kabupaten Bulungan - Iskandar, Iskandar; Mutiarin, Dyah (Journal of Governance and Public Policy, 2014)
The purpose of  this study was to describe the policy implementation Public Service Agency (BLUD) in RSUD TanjungSelor. This study uses descriptive qualitative research with data collection through the data collection process impirismove from facts to theory building. Results of  research policy implementation BLUD in RSUD Tanjung Selor show thatSPM has not run optimally meets standards and criteria set. BLUD running quite well due to the availability of  medicalfacilities and hospital equipment, adequate human resource quality, health care procedures and treatment costs areaffordable. However, for many services still complained of  patients considered less swift in responding to complaints.A common perception among the leaders of  positive effect on the delivery of  public health services, especially fromthe aspect of  equity, and affordability of  health care. In addition coordination and functional with health agencieshelped smooth implementation of  accountable implementation. The ability of  the police still lacked discipline officers,and less friendly. Comfort aspect of  this facility is an extra burden on the patient. In the sense of  this study indicate thatthe change of  status into BLUDs at RSD Dr. Soemarno Sosroatmodjo Tanjung Selor Bulungan did not show a significantimpact on changes in the quality of service.